2018
DOI: 10.1186/s13104-018-3986-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of hypertension among adult patients in Felege-Hiwot Comprehensive Referral Hospitals, northwest, Ethiopia: a cross-sectional study

Abstract: ObjectiveThe main objective of this study was to assess the prevalence and factors associated with hypertension among adult patients in Felege-Hiwot Comprehensive Referral Hospital, northwest Ethiopia, 2018.ResultThe prevalence of hypertension in the current study area was 27.3%. Known history of cardiac problems [AOR = 6.9; 95% CI (1.24, 11.44)], alcohol consumption [AOR = 2.2; 95% CI (1.04, 5.05)], abdominal obesity [AOR = 2.3; 95% CI (1.02, 5.04)], and obesity [AOR = 4.8; 95% CI (1.12, 8.34)] were factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 22 publications
3
21
2
Order By: Relevance
“…The finding is slightly comparable to a community-based study among police officers in Bengal, India 32% [17]. The prevalence of hypertension in this study is higher than the studies in Gonder with the prevalence of 28.3% (26), Addis Ababa 31.5% [7], among a ministry of civil servants 27.3% [18], Durame 22.4%, Bahir Dar city 25.1% and 27.3% [2,19,20], Ethiopia and Hawwasa 19.6% [8,21], Jigjiga 28.3%, and Tigray 16% [22,23]. This discrepancy may be explained by the study methodology and setting difference.…”
Section: Discussionsupporting
confidence: 71%
“…The finding is slightly comparable to a community-based study among police officers in Bengal, India 32% [17]. The prevalence of hypertension in this study is higher than the studies in Gonder with the prevalence of 28.3% (26), Addis Ababa 31.5% [7], among a ministry of civil servants 27.3% [18], Durame 22.4%, Bahir Dar city 25.1% and 27.3% [2,19,20], Ethiopia and Hawwasa 19.6% [8,21], Jigjiga 28.3%, and Tigray 16% [22,23]. This discrepancy may be explained by the study methodology and setting difference.…”
Section: Discussionsupporting
confidence: 71%
“…A total of eighteen [ 22 , 25 , 27 29 , 31 , 32 , 35 , 40 , 43 , 45 – 47 , 49 – 51 , 55 , 56 ] studies included to estimate the association between BMI and hypertension. The results of the test statistics indicate that significant heterogeneity was observed between studies (I 2 = 95.41%, P-value < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that the prevalence of hypertension in Ethiopia ranged from 24.4% to 34.7%. [9][10][11][12][13] The data published by WHO showed that in 2017, 1.74% of the total deaths (or 11,050 deaths) in Ethiopia were caused by hypertension. As a result, hypertension was ranked 11th out of the top 20 causes of death in the country.…”
Section: Introductionmentioning
confidence: 99%